Optimization of vehicle flow in the road intersection of the Av. Bolognesi and the Av. Gustavo Pinto in the city of Tacna - Urbina Cantuta, Carla Maricela (2019)
The present investigation makes an analysis of the current conditions that are generated due to vehicular congestion at the intersection of the two main arterial avenues under study that occur at peak hours. The purpose of the present study is to optimize the behavior of the vehicular flow with the presentation of proposals for solutions that improve the current level of service and reduce the existing vehicular congestion in the study area.